Air pollution and health - Ayres, J. G.; Maynard, Robert, 1962-; Richards, Roy (Air pollution reviews ;, 2006)
This invaluable volume, the third in the series "Air Pollution Reviews", addresses particular questions relating to air pollution and its effect on health. It deals with the impact of nasal disease on lung exposure, how pollutants are distributed within the lung, and the uncertainties with regard to defining the dose to the lung. It takes a tangential look at the lung dose by exploring the possibility of obtaining clues from occupational medicine. Toxicologically, the book examines the possible methodology for exploring how particles and their toxicity can be investigated, and looks into the cardio-toxic effects of air pollution. The effects of pollutant mixtures are compared with those of individual pollutants. In addition, the question of the importance of acid aerosols is tackled. Epidemiologically, the book deals with the problems associated with point sources as opposed to diffuse sources of air pollution, and consider whether the health effects of air pollution can be adequately quantified. These areas, though difficult, need to be addressed, in order to develop our knowledge of the health effects of air pollution. In this volume, a strong panel of authors treats the issues. They have raised questions but at the same time succeeded in solving a number of problems.